2014
DOI: 10.1177/00333549141291s109
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Integration Effort to Reduce the Risk for Alcohol-Exposed Pregnancy among Women Attending Urban STD Clinics

Abstract: Alcohol-exposed pregnancy (AEP) is a significant public health problem in the United States. Sexually transmitted disease (STD) clinics serve female clients with a high prevalence of heavy alcohol consumption coupled with ineffective contraceptive use. Project CHOICES (Changing High-Risk AlcOhol Use and Increasing Contraception Effectiveness) is an evidence-based, brief intervention to lower risk of AEP by targeting alcohol and contraceptive behaviors through motivational interviewing and individualized feedba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…Similarly, a study that utilized both in-person and telephone-based adaptations of CHOICES interventions with women at clinics and college campuses in Wisconsin found that risk of AEP was significantly reduced, mostly due to improved contraception with minor reductions in alcohol use (Wilton et al, 2013). Women in two urban communities (Baltimore and Denver) who received the 2-session version of CHOICES also lowered their AEP risk at significant rates, and were more likely than our study to change both behaviors, finding similar results to the original CHOICES study (Hutton et al, 2014). …”
Section: Discussionsupporting
confidence: 76%
“…Similarly, a study that utilized both in-person and telephone-based adaptations of CHOICES interventions with women at clinics and college campuses in Wisconsin found that risk of AEP was significantly reduced, mostly due to improved contraception with minor reductions in alcohol use (Wilton et al, 2013). Women in two urban communities (Baltimore and Denver) who received the 2-session version of CHOICES also lowered their AEP risk at significant rates, and were more likely than our study to change both behaviors, finding similar results to the original CHOICES study (Hutton et al, 2014). …”
Section: Discussionsupporting
confidence: 76%
“…For one example, an evaluation of counseling to prevent alcohol-exposed pregnancies in two clinics had effects on sexual behavior, although it did not measure STD. 38 …”
Section: Discussionmentioning
confidence: 99%
“…At that time, OST was conducting individual CHOICES sessions using a 2-session intervention format previously tested in Baltimore and Denver STI clinics (Hutton et al, 2014), so the CHOICES Group intervention also used a two-session model. Ingersoll conducted training with four current OST CHOICES staff (2 Native and 2 non-Native) to fine-tune their MI and CHOICES intervention skills, to demonstrate how to conduct CHOICES sessions in a group format, and to provide opportunities to practice CHOICES Group skills.…”
Section: Methodsmentioning
confidence: 99%